Criminal intelligence analysis based on ontological knowledge representation model - A. Jalil, M; Mohd, F; P. Ling, C; M. M. Noor, N (International Journal of Engineering and Technology, 2018)
Nowadays, community security is an issue which is given higher priority by all agencies, aiming to reduce crime incidence. As knowledge representation is the appropriate way to apply on complex crime analysis information, hence ontology-based case matching model is proposed to represent the relationships among the knowledge. Therefore, in this study, the ontology model is developed using semantic web modelling tool, TopBraid Composer Standard Edition in order to represent the crime information with the well-defined classes and relationships. The advantage of TopBraid is the ability in offering comprehensive supports for building, managing and testing the configuration of ontology and Resource Description Framework (RDF) graphs.Â